2011
DOI: 10.3897/zookeys.100.1360
|View full text |Cite
|
Sign up to set email alerts
|

Ground beetle (Coleoptera, Carabidae) assemblages inhabiting Scots pine stands of Puszcza Piska Forest: six-year responses to a tornado impact

Abstract: Ground beetle assemblages were studied during 2003-08 in the Pisz Forest by comparing stands disturbed by a tornado to undisturbed control stands. The following exploratory questions were put forward. (1) How do the carabid assemblages change during six years following the tornado impact? (2) Does the carabid assemblage recovery begin during the six first post-tornado years? To assess the state of carabid assemblages we used two indices: the MIB (Mean Individual Biomass) and the SPC (Sum of Progressive Charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…This species is abundant in the forests of South Moravia (Šejnohová, 2006). The species dominates in the forests of Poland (Sklodowski, 2006(Sklodowski, , 2014Kwiatkowski, 2011;Sklodowski & Garbalinska, 2011;Zalewski et al, 2012). There numerous reports of finding this species in Lithuania (Tamutis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This species is abundant in the forests of South Moravia (Šejnohová, 2006). The species dominates in the forests of Poland (Sklodowski, 2006(Sklodowski, , 2014Kwiatkowski, 2011;Sklodowski & Garbalinska, 2011;Zalewski et al, 2012). There numerous reports of finding this species in Lithuania (Tamutis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The rate at which species composition changes during succession and the successional trajectory followed by the carabid assemblages depends on environmental conditions, such as soil properties (Szyszko 1986b, 1990; Schwerk 2008), dominant tree species (Du Bus de Warnaffe and Lebrun 2004), and the type of disturbance that initiated the succession (Du Bus de Warnaffe and Lebrun 2004). Indeed, the larger the newly-created gap is and the fewer trees retained, the more severe the perturbation for carabid assemblages (Koivula 2002b following timber harvest; Bouget 2005 and Skłodowski and Garbalińska 2010 following windthrow gap). As a consequence, the maintenance of a variety of successional phases of the forest cycle results in increased heterogeneity at the landscape level and, therefore greater regional carabid diversity (e.g.…”
Section: Landscape Ecologymentioning
confidence: 99%
“…Skłodowski and Garbalińska (2007) showed that carabidae assemblages markedly declined in abundance, although species richness was significantly higher in damaged stands compared to control stands after a hurricane in Puszcza piska pine forests. Skłodowski and Garbalińska (2011) emphasized that carabidae assemblages in the disturbed and control stands were different but no clear signals of recovery of carabidae assemblages were observed during a 6 year follow-up. Duelli et al (2002) found that a hurricane significantly increased carabid species richness in gaps.…”
Section: Discussionmentioning
confidence: 91%